2016
DOI: 10.1111/pin.12386
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing mesenteritis: A real manifestation or histological mimic of IgG4‐related disease?

Abstract: We present three cases of sclerosing mesenteritis and review the literature to learn whether or not sclerosing mesenteritis is an IgG4-related disease (IgG4-RD). Our patients were all adult males. Their mesenteric masses ranged from 6.5 to 14.5 cm in the greatest diameter. Tissue specimens showed moderate to severe lymphoplasmacytic infiltration with occasional eosinophils against a background of irregular fibrosis. Both obliterative phlebitis and storiform fibrosis were noted in all cases. IgG4+ plasma cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
(28 reference statements)
0
15
1
1
Order By: Relevance
“…While some authors have proposed the possibility of concurrent IgG 4 -RD and SM,12 13 no cases of SM in this review were found to fulfil all four of the IgG 4 -RD characteristic features. After examining the histopathological and clinical patterns in this limited cohort of patients, Avinscal et al 5 concluded that while some cases of SM may mimic IgG 4 -RD, IgG 4 -RD rarely affects the mesentery. As conclusions from these small studies and expert opinions are highly variable, the question of whether IgG 4 -RD can include the diagnosis of SM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some authors have proposed the possibility of concurrent IgG 4 -RD and SM,12 13 no cases of SM in this review were found to fulfil all four of the IgG 4 -RD characteristic features. After examining the histopathological and clinical patterns in this limited cohort of patients, Avinscal et al 5 concluded that while some cases of SM may mimic IgG 4 -RD, IgG 4 -RD rarely affects the mesentery. As conclusions from these small studies and expert opinions are highly variable, the question of whether IgG 4 -RD can include the diagnosis of SM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, SM includes degeneration of fat cells leading to areas of calcification, occasional infiltration with lipophages, macrophages, plasma cells and a proliferative of fibroblasts. While IgG 4 -RD can affect any organ,4 many investigators purport that IgG 4 -RD, if ever, affects the small bowel mesentery 5. However, cases of SM in patients with elevated IgG 4 -RD have been reported 10 12 13…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-related SM was reported by Minato et al 4 Avincsa et al reported three cases of idiopathic SM and suggested that SM shares histological features with IgG4related disease, but most SM cases are less likely to be IgG4-related disease. 5 All four Japanese cases reported thus far had a benign clinical course. 4,5 The tumor spontaneously regressed in two cases and was surgically resected without relapse.…”
Section: To the Editormentioning
confidence: 95%
“…4,5 The tumor spontaneously regressed in two cases and was surgically resected without relapse. 4,5 The patient in the present case died due to severe diarrhea, renal failure, and intestinal perforation. Superior mesenteric artery syndrome may be caused by SM.…”
Section: To the Editormentioning
confidence: 99%
“…The segments of the small intestine may show slight thickening and elongation. The most common symptoms include fever, abdominal pain, and malaise [23].…”
Section: Diagnosismentioning
confidence: 99%